Quality Management Of Facilities And Infrastructure At Madrasa - wiratmoko, wiratmoko -; Kholid, Idham; Fauzan, Ahmad (Universitas Islam Negeri Raden Intan Lampung, 2022)
Facilities and infrastructure are important components of an efficient educational process in schools. The management of educational facilities and infrastructure must be done in order to guarantee the smooth operation of the madrasa's facilities and infrastructure. The purpose of this study is to describe the quality management of facilities and infrastructure at Madrasa Aliyah Negeri 1 Pringsewu, Lampung, Indonesia. The principal of Madrasa Aliyah Negeri 1 Pringsewu, the administrative staff, the committee, and the vice principal of facilities and infrastructure are the study's sources of data. Observation, documentation, and interviews were used to collect the data. The analysis of the study's data included data reduction techniques, data visualization, and conclusion drawing or verification. Triangulation was used to check the validity of the data in the interim. Planning, doing, checking, and action is all used to manage the quality of the facilities and infrastructure at Madrasa Aliyah Negeri 1 Pringsewu, Lampung, Indonesia, based on the research's findings. After determining the needs through analysis, procurement is done by offering opportunities to partners. Maintenance of facilities and infrastructure is done by collecting data on the facilities and infrastructure owned, then organizing and taking special care of electronic objects. Finally, follow-up is done by using and removing facilities and infrastructure.